Improving Biological Nitrogen Fixation to Improve Soil Nutrient Status - Lakesh K. Sharma; Ayush K. Sharma; Andrew Ogram; Hardeep Singh (EDIS)
The chemical reduction of atmospheric nitrogen (N2) by hydrogen for incorporation into plant tissue is known as N fixation. Along with the carbon, N has a role in maintaining the optimum source and sink ratio, which ensures crop growth and biological yield. N is available in great concentration (≈80%) in the atmosphere in N2 form, but plants cannot absorb or uptake N in N2 form. N fertilizers are available in straight, mixed, and nano and liquid fertilizers. These approaches are not enough, though, to maximize N use efficiency to 100%. A significant amount of nitrogen is still lost in air and water bodies, leading to multiple negative impacts to the environment. Therefore, N fixation through the crop itself is a practical approach to reduce the use of synthetic nitrogen and enhance the sustainability of the food production systems. This publication discusses various methods for BNF and its importance to the sustainability of crop production.